The functional graphene/epoxy resin composites prepared by novel two-phase extraction towards enhancing mechanical properties and thermal stability - Zhu, Wenfeng; Wang, Qianxi; Zhang, Pengchao; Li, Lei; Zhang, Li; Li, Houbu; Ding, Lekang; Jin, Zunlong; Li, Peipei; Zhang, Jiaoxia (Frontiers in Chemistry, 2024)
Epoxy resins, known for their excellent properties, are widely used thermosetting resins, but their tendency towards brittle fracture limits their applications. This study addresses this issue by preparing graphene oxide via the Hummer method, modifying it with hyperbranched polyamide ester, and reducing it with hydrazine hydrate to obtain functionalized graphene. This functionalized graphene improves compatibility with epoxy resin. Using a novel two-phase extraction method, different ratios of functionalized graphene/epoxy composites were prepared and tested for mechanical properties and thermal stability. The results showed significant improvements: the tensile strength of composites with 0.1 wt% functionalized graphene increased by 77% over pure epoxy resin, flexural strength by 56%, and glass transition temperature by 50°C. These enhancements, attributed to the improved compatibility between graphene and epoxy resin, demonstrate the potential of functionalized graphene to mitigate the brittleness of epoxy resins, expanding their application potential.